The Impact of Narcissistic Leader on Subordinates and Team Followership: Based on “Guanxi” Perspective - Wang, Lin (Frontiers in Psychology, 2021)
The impact of COVID-19 makes the enterprise feel enormous uncertainty. Studies have shown that narcissistic individuals are more likely to become leaders in uncertain situations. While, few studies paid attention to the relational mechanism linking narcissistic leader with subordinate and team attitudes and behaviors. Based on the "Guanxi" and dominance complementarity theory，we examined the influencing mechanism of narcissistic leader on subordinates and team followership. Two-wave data collected from 326 employees in the manufacturing and technology industry in China supported our hypothesized model. We have found that narcissistic leaders have negative impact on subordinates’ followership and team followership; Supervisor-subordinate Guanxi and team leadership relationship identity play partial mediating role between narcissistic leadership and subordinate and team followership. Furthermore, individual and team values play a moderating role in the process of influencing mechanism. In other words, the higher the individual tradition and team power distance, the less negative impact of leader narcissism on supervisor-subordinate Guanxi and team leadership relationship identity. Theoretical and practical implications are discussed. We also offer several promising directions for future research.